Oscillating heat pipe cooler for heat-generating elements of electronics - Alekseik, E. S.; Kravets, V. Yu. (Technology and design in electronic equipment, 2013)
The article presents a newly-developed compact heat removal system (HRS) with water used for coolant, operable in any position in space. In conditions of forced convection at output power of 120 Wt (160 Wt input power) thermal resistance of the HRS is 0.1 K/Wt and the system provides the average temperature of the cooled object over the range of 58 to 60°C. Heat transfer characteristics of the HRS can be improved, as there is potential for its modification.